Analisis Pengaruh Tingkat Suku Bunga Dan Pengeluaran Pemerintah Terhadap Investasi Di Indonesia Periode Tahun 2014-2023 - Saragi, Jonathan Brando; Nadia Vega Br Surbakti; Natalia; Tio Nardo Gulo (CV. Ulil Albab Corp, 2024)
This study aims to analyze the impact of Interest Rates and Government Expenditures on Investment in Indonesia during the 2014–2023 period using a quantitative method with multiple linear regression analysis. The data used in this research are secondary data obtained from the Central Bureau of Statistics (BPS) and Bank Indonesia, processed using SPSS software. The simultaneous test results show that Interest Rates and Government Expenditures jointly have a significant effect on Investment, with an F statistic value of 90.047 and a significance level of 0.000 < 0.05. However, on a partial basis, only Government Expenditures significantly influence Investment (t statistic = 11.165; sig. = 0.000 < 0.05), while Interest Rates do not show a significant effect (t statistic = 1.493; sig. = 0.0895 > 0.05). These findings indicate that fiscal policy, through Government Expenditures, plays a more dominant role in driving investment levels compared to monetary policy through Interest Rates.